Revisiting Agroforestry for Building Climate Resilient Communities: A Case of Package-Based Integrated Agroforestry Practices in Nepal - Kishor Aryal; Prakash Singh Thapa; Dhananjaya Lamichhane (Emerging Science Journal, 2019)
Agriculture based livelihoods in developing countries are bearing significant negative impacts due to climate change. In this scenario, agroforestry is one of the best alternatives to cope with climate change and disaster risks. However, the agroforestry approaches adopted in the past were sectoral and partial, and were insufficient to contribute to socio-economic wellbeing and resilient communities. Nepal has been implementing package-based integrated agroforestry since 2016. It is a project approach to advance agroforestry practices by including disaster mitigation, land and water management, and community development activities. This paper reflects on the process and outcomes of the agroforestry practices, implemented by the government in seven super zones of Nepal. The programs have shown fairly satisfactory output in building adaptive capacity to climate change, awareness and active participation in agroforestry development activities. This paper reveals that agroforestry alone cannot be sustained, and hence, it has to be integrated with land productivity enhancement, natural resource management, climate change adaptation, and livelihood support in addition to tree planting in agricultural lands. This paper is crucial in understanding the scope of the package-based integrated agroforestry approach to build climate resilient communities.